SELF-POTENTIAL FOR FIX GEOMETRY BURIED BODY USING GAUSS NEWTON METHODS AND ITS APLICATION IN LABORATORY SCALE - (NIM : 90213020), MELDAWATI
Self-Potential (SP) method is the simplest method of geophysical measurement equipment. This methods can be be introduced to high school students as an enrichment material on the application of physics in exploration geophysics. SP measurements carried out by a laboratory scale using 60cmx30cmx30 cm sized sandbox and spherical and cylindrical buried bodies . The result of measurement can be simply interpreted using forward SP with Excel VBA and simple Gauss Newton inversion method. Interpretation of the simulation program forward SP was taken by varying the parameter values anomalous bodies that generate the forward curve approaching curve measurement results. While the Gauss Newton inversion was given damping factor to produce the minimum norm. From the inversion results , parameter point of origin has the smallest error value of 2.5% for spherical bodies and 5.7% for spherical bodies. While the geometry parameter q has the greatest error value 66% for spherical buried bodies and 43% for cylindrical buried bodies .